Exploring Mechanical Properties Using the Hydraulic Bulge Test and Uniaxial Tensile Test with Micro-Samples for Metals - Jian Bao; Haoran Ding; Zhiquan Zuo; Jian Peng (Metals, 2024)
The hydraulic bulge test with micro-samples is expected to be useful in the damage assessment of long-service-period metals to understand the degeneration of their mechanical properties. Since the hydraulic bulge test has a different stress state from the classical uniaxial tensile test, we need to understand their correlation and differences. In this study, the hydraulic bulge test and the uniaxial tensile test are employed to analyze the mechanical properties of three typical metals used in pressure vessels: 316L, 16MnDR, and Q345R. By utilizing Kruglov’s vertex thickness and Panknin’s curvature radius equivalent, the pressure–displacement curves from the hydraulic bulge test are converted into biaxial stress–strain curves. Based on the equivalent plastic energy model, the biaxial stress–strain curves are converted into uniaxial stress–strain curves with an error less than 10% in the strain hardening stage, achieving the unified characterization of mechanical properties under different stress states. Moreover, the hydraulic bulge test provides a more extensive strain hardening stage, and the fracture strains are 9–16.5% larger than those of uniaxial tensile test. This paper provides a reference for using the hydraulic bulge test with micro-samples in studying the mechanical properties and presents the advantages of this novel test method.